TRANSFORMATION OF SOCIAL MEDIA MARKETING UNDER THE INFLUENCER MARKETING DEVELOPMENT - Reshetnikova, Olha (Current Problems of Sustainable Development, 2026)
The article examines the transformation of social media marketing under the influence of influencer marketing development in the context of digitalization and changes in consumer behavior. The relevance of the research is determined by the rapid growth of social media platforms as communication channels between businesses and consumers, as well as by the increasing impact of influencers on purchasing decisions, brand perception, and audience engagement. Modern consumers demonstrate a higher level of trust in personalized recommendations and authentic digital content than in traditional advertising formats, which requires companies to reconsider existing approaches to marketing communications and develop new strategies for interaction with target audiences. The purpose of the study is to investigate the transformational processes occurring in social media marketing through cooperation with influencers, to identify the main mechanisms of influencer impact on consumer behavior, and to develop practical approaches to improving marketing communication strategies in the digital environment. Particular attention is paid to the role of influencers as intermediaries between brands and audiences, as well as to the growing importance of authenticity and personalized communication in modern marketing activities. The study is based on general scientific methods, including analysis, synthesis, comparison, systematization, and generalization. These methods were used to identify the main characteristics of influencer marketing, classify influencers, and determine the mechanisms of their influence on consumer behavior in social networks. The results of the study demonstrate that influencer marketing has become a strategically important component of modern digital marketing. It has been established that the effectiveness of influencer cooperation depends not only on audience reach but also on audience engagement, trust, value congruence between the influencer and the brand, and the quality of content integration. The study identifies the main mechanisms of influencer impact, including trust formation, emotional influence, social imitation, and informational influence. The practical  value of the obtained results lies in the development of recommendations for creating effective influencer marketing strategies, improving influencer selection processes, integrating influencer campaigns into overall marketing communication systems, and applying analytical tools for evaluating campaign performance in digital business environments.
Keywords: social networks; SMM; influencer marketing; opinion leaders; consumer behavior; brand communications